Association between oral microbiome and seven types of cancers in East Asian population: a two-sample Mendelian randomization analysis - Feng, Kexin; Ren, Fei; Wang, Xiang (Frontiers in Molecular Biosciences, 2023)
The oral microbiome has been intricately linked to various pathological conditions, notably cancer, though clear causal links remain elusive. This study aimed to investigate the potential causal relationships between the oral microbiome and seven major cancers: breast, lung, pancreatic, colorectal, gastric, ovarian, and prostate cancers, leveraging Mendelian randomization (MR).A two-sample MR analysis was conducted using genome-wide association study (GWAS) data specific to oral microbiota in individuals of East Asian descent. Single nucleotide polymorphisms (SNPs) independent of confounders served as instrumental variables (IVs) to deduce causality. MR methodologies such as the inverse variance weighted (IVW) method, weighted median (WM) method, and Mendelian randomization-Egger (MR-Egger) method were employed. The study utilized datasets encapsulating a multitude of cancer cases and controls, focusing on Asian populations.Results: Our analysis revealed intricate associations between specific bacterial genera of the oral microbiome and diverse cancers. Notably, Fusobacterium showed mixed associations with various cancers, while genera like Prevotella and Streptococcus exhibited nuanced roles across malignancies.The genus Aggregatibacter demonstrated a multifaceted influence, positively correlating with some cancers while inhibiting others.Our findings underscore the profound implications of the oral microbiome in systemic malignancies, suggesting potential modulatory roles in cancer etiology. These insights, though preliminary, accentuate the need for deeper exploration and could pave the way for novel therapeutic strategies.Globally, cancer incidence and mortality rates are escalating alarmingly, with projections indicating about a 50% surge in the global oncologic burden over the next two decades (1). As delineated in the Cancer Statistics 2022 report (2), prostate cancer (PCa), lung cancer (LC), and colorectal cancer (CC)